Comparative investigation of the fatigue limit of additive-manufactured and rolled 316 steel based on self-heating approach. (January 2020) - Cao, Yinfeng; Moumni, Ziad; Zhu, Jihong; Zhang, Yahui; You, Yajun; Zhang, Weihong
Highlights: Fatigue properties of AM and rolled 316 steel are investigated using self-heating approach. The difference of fatigue properties is analyzed from the viewpoint of microstructure. A computational model based on CPFEM and mesoscopic fatigue criterion is constructed. Abstract: In this paper, fatigue properties of additive-manufactured (AM) 316 steel are investigated by the rapid fatigue limit evaluation method based on self-heating experiments. To this end, a series of tensile cycling experiments are carried out on AM 316 steel specimens; temperature variation resulting from the self-heating phenomenon is recorded by an infrared thermography (IR) camera and fatigue limit is deduced. To compare with the properties of traditionally processed materials, the fatigue limit of rolled 316 steel is also investigated using the same procedure. The experimental results show that the AM 316 steel has a higher fatigue limit than rolled one. In order to interpret this result, microstructures of AM and rolled 316 steel are characterized by metallurgical microscope and X-ray diffractometer (XRD). Furthermore, a crystal-plasticity-fatigue-based model is developed and cyclic simulations are carried out. The difference of fatigue limit between AM and rolled 316 steel is discussed experimentally and numerically from microscopic viewpoint, including grain size and dislocation density. It is shown that: (1) the AM process induces coarsening of the grains and reduction of ductility, and (2) ductility plays a much important role than refining grain size on fatigue limit. For this reason, AM 316 steel presents a higher fatigue limit than 316 rolled steel.